Javna služba in poslovanje notarske dejavnosti v Sloveniji - Omerzu, Nataša (Pravnik, 2015)
In everyday life we sooner or later come across a notary service, either solely connected to the verification of certain signatures or otherwise. For a long time the public remained ignorant regarding the actions of notaries, but later on became increasingly interested in their business. In its work notaries must coordinate the interests of all parties, be impartial and effective. They must act in accordance with the Slovenian Notaries Act and Notary Tariff. With e-commerce everything became increasingly accessible. On the other side, information on the performance of their actions did not become more accessible. Income data which can be found on individual webpages, do not disclose their earnings, as the costs and obligations of notaries still remain confidential. Great efforts of the public have been made to reveal such information either by the Chamber of Notaries of Slovenia or other organizations.
Keywords: civil law notary; dobiček; dohodki; finančno poslovanje; javnost; notariat; notarji; notarske tarife; Slovenia; Slovenija